2013
DOI: 10.1371/journal.pone.0075389
|View full text |Cite|
|
Sign up to set email alerts
|

The Transcriptional Regulator Np20 Is the Zinc Uptake Regulator in Pseudomonas aeruginosa

Abstract: Zinc is essential for all bacteria, but excess amounts of the metal can have toxic effects. To address this, bacteria have developed tightly regulated zinc uptake systems, such as the ZnuABC zinc transporter which is regulated by the Fur-like zinc uptake regulator (Zur). In Pseudomonas aeruginosa, a Zur protein has yet to be identified experimentally, however, sequence alignment revealed that the zinc-responsive transcriptional regulator Np20, encoded by np20 (PA5499), shares high sequence identity with Zur fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 52 publications
5
75
0
Order By: Relevance
“…As bacterial responses to chelating agents are sometimes ambiguous 56 , we analyzed growth of a PA14 mutant strain lacking znuA in a chemically defined minimal medium containing only contaminant traces of zinc. In line with the results of Ellison et al 55 , the mutant strain exhibited a modest growth defect (Figure 1A) and a more marked phenotype could be observed only in minimal medium agar plates supplemented with EDTA (Figure 1b), a result possibly favored by the ability of the solid agar support to limit zinc availability to bacteria 57 . The small impact of znuA deletion on bacterial growth is accompanied by the substantial equality of the intracellular zinc content between the wild-type and the mutant strains grown in minimal medium (Figure 4).…”
Section: Discussionsupporting
confidence: 89%
“…As bacterial responses to chelating agents are sometimes ambiguous 56 , we analyzed growth of a PA14 mutant strain lacking znuA in a chemically defined minimal medium containing only contaminant traces of zinc. In line with the results of Ellison et al 55 , the mutant strain exhibited a modest growth defect (Figure 1A) and a more marked phenotype could be observed only in minimal medium agar plates supplemented with EDTA (Figure 1b), a result possibly favored by the ability of the solid agar support to limit zinc availability to bacteria 57 . The small impact of znuA deletion on bacterial growth is accompanied by the substantial equality of the intracellular zinc content between the wild-type and the mutant strains grown in minimal medium (Figure 4).…”
Section: Discussionsupporting
confidence: 89%
“…1C). These data indicate that Zur serves as a transcriptional repressor, and this is in line with what other investigators have observed, with Zur negatively controlling znu expression in several diverse bacteria, including Bacillus subtilis (26), Escherichia coli (27), and Pseudomonas aeruginosa (28). Of interest, mRNA levels for zntA, which encodes the putative Zn exporter, were also significantly elevated in the zur mutant.…”
Section: Resultssupporting
confidence: 91%
“…Like many bacteria (Patzer and Hantke, 1998), it possesses a Zn 21 uptake system known as ZnuABC (Ellison et al, 2013), made up of members of the ABC transporter family of proteins. Like many bacteria (Patzer and Hantke, 1998), it possesses a Zn 21 uptake system known as ZnuABC (Ellison et al, 2013), made up of members of the ABC transporter family of proteins.…”
Section: Zinc (Zn)mentioning
confidence: 99%
“…Concerning the uptake across the cytoplasmic membrane, different approaches have shown that P. aeruginosa has in its genome different Zn 21 uptake pathway. Like many bacteria (Patzer and Hantke, 1998), it possesses a Zn 21 uptake system known as ZnuABC (Ellison et al, 2013), made up of members of the ABC transporter family of proteins. This system is composed of a Zn-binding periplasmic protein (ZnuA, PA5498), an inner membrane permease (ZnuB, PA5501) and an ATPase (ZnuC, PA5500).…”
Section: Zinc (Zn)mentioning
confidence: 99%